The Effect of Service Quality and Delivery Service on Consumer Satisfaction at Pizza Hut Paramount Bintaro Branch - Tita Setiawati (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine service quality and delivery service on customer satisfaction at Pizza Hut Paramount Bintaro Branch. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. This study shows that the quality of service significantly affects customer satisfaction by 45.0%, hypothesis testing is obtained t count > t table or (7.062 > 2,000). Delivery service significantly affects consumer satisfaction by 50.8%; hypothesis testing is obtained t count > t table or (7,942 > 2,000). Service quality and delivery service simultaneously significantly affect customer satisfaction with the regression equation Y = 5.789 + 0.368X1 + 0.501X2. The contribution of influence is 63.6%.